2020
DOI: 10.1109/mra.2019.2928823
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impact of Social Robots: How Anthropomorphism Boosts Performances

Abstract: Applying Research on Human Presence and Attention Humanoid robots will likely take on increasingly important roles the lives of millions of people worldwide [1], [2]. While tremendous progress has been made in robotics science, the influence that these new humanoid robots may have on human cognition itself remains poorly understood. Evidence indicates [3]-[6] that the presence of a humanoid robot can lead to effects similar to those caused by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 74 publications
3
32
0
1
Order By: Relevance
“…Second, in agreement with our hypotheses, we found higher Sociability, Agency, and Animacy attribution in parallel to less Disturbance when evaluating the social robot compared to the non-social one. These results are in line with previous studies using the same methodology in which participants attributed more anthropomorphic characteristics to the robots after a social-compared to a non-social interaction (Spatola et al 2018, Spatola et al, 2019. However, comparing to these previous results, the present scale seems more sensitive than those used in the above-mentioned study.…”
Section: C Dsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, in agreement with our hypotheses, we found higher Sociability, Agency, and Animacy attribution in parallel to less Disturbance when evaluating the social robot compared to the non-social one. These results are in line with previous studies using the same methodology in which participants attributed more anthropomorphic characteristics to the robots after a social-compared to a non-social interaction (Spatola et al 2018, Spatola et al, 2019. However, comparing to these previous results, the present scale seems more sensitive than those used in the above-mentioned study.…”
Section: C Dsupporting
confidence: 92%
“…Studies showed that mechanistic dehumanization results in behavior such as indifference or lack of empathy towards individuals (Haslam, 2006;Haslam & Loughnan, 2014;Kteily, Bruneau, Waytz, & Cotterill, 2015). This de-humanization dimension has proved to be a reliable measure of social evaluation to predict socio-cognitive processes in an HRI situation, especially the Human nature/Mechanistic de-humanization distance measure (Spatola, Belletier, et al, 2019;Spatola, Monceau, & Ferrand, 2019).…”
Section: Relevant Insights From Social-cognitive Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…The experimenter asked NAO to grasp an object and to put it in a marked box. After this sequence, participants rated the robot on two scales presented in a counterbalanced order: the Robotic Social Attribute scale (RoSAS) [12] and the De-humanization scale based on Haslam taxonomy [29,42].…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the relationship between implicit attitudes towards robots and explicit perceptions of robots, along with the semantic priming task (implicit measure), we first assessed participants' self-reported attitudes, explicit semantic distance between robots and humans, and perceived robot anthropomorphism [41].To evaluate individuals' representation of robots, we used the theory of dehumanization that describes a disposition towards others in which the observer deprives the other of social or human characteristics. The dehumanization process, theorized by Haslam [29] is based on a modulation of the distance between the representation of what defines the concept of a 'human' and what defines the concept of an 'other' [29], and has previously been proved to be a reliable measure of robot evaluation [42].…”
Section: The Change In the Intrinsic Representation Of Robotsmentioning
confidence: 99%